CHARACTERIZATION AND QUALITY ASSESSMENT OF INDONESIAN COMMERCIAL BIOFERTILIZERS - Husen, Edi Husen; Simanungkalit, R.D.M.; Saraswati, Rasti; ., Irawan (Indonesian Journal of Agricultural Science, 2007)
Biofertilizers currently sold in the market are not labeled witha distinct quality standard. As such, farmers may buy low qualitybiofertilizers, which can reduce their profit and trust on the benefitof biofertilizers. This paper presents the characteristics of variousproducts of commercial biofertilizers as well as farmersâ knowledgeand experience on the products. The study was carried out in2004-2006 by collecting and analyzing data on registered commercialbiofertilizers, checking their availability at the market(39 agricultural shops), and interviewing farmers on their knowledgeand experience on the use of biofertilizers on various farmingsystems in Bandung District, West Java (86 respondents) andSemarang District, Central Java (77 respondents). The quality ofbiofertilizers was tested in the laboratory based on microbialdensity and its functional (phenotypic) traits. The study showedthat amongst various brands of biofertilizers commercialized,41 brands of them have been officially registered as commercialproducts. Two brands of other biofertilizers found in agriculturalshops were registered as organic or inorganic fertilizers. In general,each biofertilizer contained two or more microbial strains andwas claimed to have multiple functions. However, most of them(>90%) were not labeled with expiry date information. Macronutrientcontents (NPK) of some microbial carriers were almostequal to those of organic fertilizers. Around 38% of respondentsin Bandung knew biofertilizers and less than 10% have ever usedthem. In Semarang, however, familiarity and personal experienceof the respondents were much lower, i.e. 10% and 3%, respectively.About 67% and 50% of agricultural shops in Bandung andSemarang sold biofertilizers, respectively. Laboratory analysesshowed that microbial density of five biofertilizers tested waslower than that of product specification, although most of themwere positive for N-fixing and P-solubilizing traits. Some microbialstrains contained less than 103 cfu based on the dilution leveltesting. These figures imply the urgent need to improve theexisting quality standard system of biofertilizers including itscontrol mechanisms.